Atomic structure, electronic states, and optical properties of epitaxially grown β-Ga2O3 layers. (August 2018) - Zatsepin, D.A.; Boukhvalov, D.W.; Zatsepin, A.F.; Kuznetsova, Yu A.; Gogova, D.; Shur, V.Ya; Esin, A.A.
Abstract: β-Ga2 O3 epitaxial layers of different thicknesses were grown and characterized by X-ray photoelectron (XPS) and optical reflectance spectroscopies. The XPS electronic structure mapping and the valence band spectra demonstrate the relationship between the time of deposition of the β-Ga2 O3 epitaxial layers and the number of defects. Counterintuitively, the thinnest films (8 nm) fabricated within 2 min were almost defect-free in contrast to the thickest ones formed at 10 and 30 min. Density functional theory modeling predicted rather high (several eV) formation energies of all types of defects in bulk β-Ga2 O3 and the energetic favorability of the formation of the interstitial gallium defects instead of the standard oxide oxygen vacancies on the surface. This uniqueness of β-Ga2 O3 could be explained by the small ionic radii of gallium and appeared to be the cause of the increase in the number of defects with the time of growth. Highlights: β-Ga2O3 epilayers were studied by XPS and optical spectroscopies combined with DFT-calculations. The origin of oxygen defects in these layers was established and modelled. A band-gap increasing due to particles size-effect is observed. The advatage of the MOVPE technology for epitaxial growth of β-Ga2O3 epilayers is shown.